Oligomerization of Chemical and Biological Compounds - Lesieur, Claire (IntechOpen, 2014)
Many thanks to the authors for high quality chapters and to the referees for helping improve the manuscripts. The book is interdisciplinary, it covers fields from organic chemistry to mathematics, and raises different aspects of oligomerization. It is a great source of information as every chapter introduces general knowledge and deep details. Mixing communities is to instigate novel ideas and hopefully help looking at oligomerization with new eyes.